Inovasi Pembelajaran PPKN Berbasis Teknologi dalam Menanamkan Sikap Toleransi - Muthi’ah Lathifah; Jojor Mindo Manullang; Salwa Andini; Reylan Sinaga; Murniwati Lase; Yusniar Yusniar; Jamaludin Jamaludin (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The Civics Education (PKn) subject is one of the courses that holds a strategic and important role in shaping the multicultural traits and attitudes of students, with the expectation that each individual can become a good person. In the era of globalization and the advancement of information technology, the challenges in instilling an attitude of tolerance are increasingly complex. Therefore, innovation in PKn teaching methods is an urgent need. Technological advancements offer new opportunities in the educational world. The use of technology in learning can enhance the effectiveness and efficiency of the teaching-learning process, as well as make learning more engaging and relevant for students. Technology-based PKn learning innovations can be a solution to instill tolerance attitudes in a more interactive, collaborative, and contextual way. The research method used is qualitative, a research model that utilizes descriptive data in the form of written or spoken language from observable people and actors. This qualitative research is conducted to explain and analyze the phenomena of individuals or groups, events, social dynamics, attitudes, beliefs, and perceptions. Interview and observation results show that at SMP NEGERI 35 MEDAN, the application of technology in Civics Education has successfully instilled an attitude of tolerance well. Media such as PowerPoint, images, and videos are used to facilitate students' understanding of the material, and teachers' examples become a reflection of students' behavior. However, there are obstacles in the form of limited facilities and infrastructure, as well as challenges in maintaining students' focus during lessons. These challenges can be overcome by using engaging learning media that can stimulate students' activity.